Potential impact on kidney infection: a whole-genome analysis of Leptospira santarosai serovar Shermani - Chou, Li-Fang (Emerg Microbes Infect, 2014)
Leptospira santarosai serovar Shermani is the most frequently encountered serovar, and it causes leptospirosis and tubulointerstitial nephritis in Taiwan. This study aims to complete the genome sequence of L. santarosai serovar Shermani and analyze the transcriptional responses of L. santarosai serovar Shermani to renal tubular cells. To assemble this highly repetitive genome, we combined reads that were generated from four next-generation sequencing platforms by using hybrid assembly approaches to finish two-chromosome contiguous sequences without gaps by validating the data with optical restriction maps and Sanger sequencing. Whole-genome comparison studies revealed a 28-kb region containing genes that encode transposases and hypothetical proteins in L. santarosai serovar Shermani, but this region is absent in other pathogenic Leptospira spp. We found that lipoprotein gene expression in both L. santarosai serovar Shermani and L. interrogans serovar Copenhageni were upregulated upon interaction with renal tubular cells, and LSS19962, a L. santarosai serovar Shermani-specific gene within a 28-kb region that encodes hypothetical proteins, was upregulated in L. santarosai serovar Shermani-infected renal tubular cells. Lipoprotein expression during leptospiral infection might facilitate the interactions of leptospires within kidneys. The availability of the whole-genome sequence of L. santarosai serovar Shermani would make it the first completed sequence of this species, and its comparison with that of other Leptospira spp. may provide invaluable information for further studies in leptospiral pathogenesis.